PRINCIPLES OF THE DETERMINATION ENERGY INTENSITY OF THE AGRICULTURAL PRODUCTS - Erhan F.; Rotari V.; Mocanu A. (Problems of the Regional Energetics, 2010)
A set of energy resources is consumed in the primary production and conversion process of agricultural product. Minimal quantity of energy required for the production of agricultural product unit is considered by the notion of energy intensity of agricultural products.